PENGARUH LATIHAN INCREMENTAL VERTICAL HOP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA SMP NEGERI 24 PEKANBARU - Zelva neni ernita; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: From the observation of researchers in the field at the men’s volleyball team smp country 24 pekanbaru.There was some weaknesess that seem in training and competition soccer, that is infirmity not optimal in volleyball. That there are still many shortcomings limb muscle during jump. This is apparent when perfoming a smash and block,men’s volleyball team so smp country 24 pekanbaru often suffered defeat on the pitch. The purpose of this research is to know effect of a workout incremental vertical hop on the leg muscle explosive power in men’s volleyball team smp country 24 Pekanbaru. The population in this research is 12 peoples by using the total sampling, so that the sample totaled were 12 peoples. Instruments in this research  is vertical jump test. Data were analyzed by using tes-t based on the test prodces tcount=4,723 with ttabel=1,796 and than 14Ha"> be accepted, on alfa ( 14Î±)"> 0,05. It can be concluded that there are significan incremental exercise vertical hop on leg muscle explosive power in mens’s volleyball team smp country 24 Pekanbaru. Keywords: Incremental vertical hop, leg muscle explosive power